Microbiological Quality Test of Food at Market Restaurant in Gorontalo City Market - Eman Rahim; Rahman Suleman (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Market food is very popular with the people of Indonesia because the price is very affordable, tastes good and has many variations. However, market food processing often ignores cleanliness starting from the processing process to the presentation so that it can cause food to be contaminated with Escherichia coli and Salmonella sp. bacteria. Food contaminated with bacteria if consumed can harm digestion so it can also cause diarrhea. The growth of these microbes can cause food to spoil making it unfit to eat and cause poisoning in humans and even death. This study aims to examine the quality of food from microbiological exposure. This research is an experimental study using the cup count method or the pour method to analyze the microbiological quality of food ingredients with 16 samples, namely Block 8 and Block 11 in the Central Market of Gorontalo City conducted from September to October 2020. Based on the test results with 3 repetitions at different times, it was obtained that samples that did not meet the requirements were in Block 8 RM 2 in the form of woku fish, and in Block 11 there were RM 1, namely chicken curry and RM 2, namely fried fish. Keyword: Bacteria, Escherichia coli, Food Market, Salmonella sp